Design of a Module for Cultivation of Tuberous Plants in Microgravity: The ESA Project “Precursor of Food Production Unit” (PFPU) - Paradiso, Roberta; Ceriello, Antonio; Pannico, Antonio; Sorrentino, Salvatore; Palladino, Mario; Giordano, Maria; Fortezza, Raimondo; De Pascale, Stefania (Frontiers in Plant Science, 2020)
Human colonization of Space requires the efficient cultivation of higher plants in Bioregenerative Life-Support Systems (BLSSs), where plants have the role to regenerate air, recycle human waste and provide fresh food for the crew. The use of hydroponic systems in controlled climatic conditions, and the selection of suitable genotypes for the specific environment help to improve the plant growth and yield. We hypothesized that plant performance could be further maximised by exploiting the action of plant growth-promoting organisms (PGPOs). However, the effects of PGPOs on plant physiology have been scarcely investigated in hydroponics. We evaluated the effects of a PGPOs mix, containing bacteria, yeasts, mycorrhiza and trichoderma beneficial species on plant growth, leaf anatomy and photosynthesis of soybean ‘Pr91m10’ in closed-loop recirculating nutrient film technique (NFT). Plants were grown in growth chamber under semi-aseptic conditions at inoculated at seed, seedling and plant stages, and compared to non inoculated control plants. Inoculation with PGPOs improved plant growth and seed yield. Starting from the reproductive phase, the rate of leaf net photosynthesis was higher in inoculated plants compared to controls, consistent with the higher photochemical efficiency; conversely no difference in leaf chlorophyll content was found. Light and epi-fluorescence microscopy revealed that modifications in plant behaviour were also due to alterations in leaf functional anatomical traits linked with gas exchange. Specifically, in inoculated plants, leaves showed higher density of smaller stomata, a thicker palisade parenchyma, and larger intercellular spaces in the mesophyll, compared to non inoculated plants. Our results confirm that PGPOs may confer benefits in growth and productive performance as well as in photosynthetic traits of soybean plants even in hydroponics (i.e. recirculating NFT), prefiguring potential application of beneficial microorganisms in plant cultivation in hydroponics, particularly in extreme environments such as Space.